A Survey on Geographic location routing and forwarding strategies of VANET and WSN based on NDN. Issue 1 (January 2021) - Hou, Saifeng; Hu, Yuxiang; Tian, Le
Abstract: Named-data Network (NDN) is a new network architecture, and its purpose is to achieve network architecture from the host-centric to the data-centric. NDN uses the data name of the application to communicate directly. Since the data name is defined by the application and unrelated to the connection, it relieves the need for IP address configuration, so as long as the physical connection exists, data exchange can occur. The NDN-based forwarding mechanism is very important for effective communication in Vechicle Ad-hoc Network (VANET) and Wireless Sensor Network (WSN). Location-based routing and forwarding utilizes the location information of neighboring nodes or destination nodes to improve the efficiency of routing search. The paper mainly discusses the geographical routing and forwarding strategies of NDN-based VANET and WSN and the existing problems, and proposes future challenges for NDN routing and forwarding.